Understanding the intention to adopt artificial insemination technology in pig by tribal farmers - SHARMA, PH ROMEN; SINGH, MAHAK; SINHA, PANKAJ KUMAR; KUMAR, BAGISH; MOLLIER, R TALLI; RAJKHOWA, D J (The Indian Journal of Animal Sciences, 2021)
The study used Theory of Planned Behaviour (TPB) to understand the underlying factors for the intention to adopt artificial insemination (AI) technology in pig by the tribal farmers of Nagaland. Responses from a survey of 72 tribal farmers of Nagaland revealed a strong intent to adopt artificial insemination in pig which is driven by strong favourable attitude towards the technology and strong approval from referent groups for the artificial insemination in pig. Perceived behavioural control seems to be the main discriminating drivers among the theory of planned behaviour constructs for the intention to adopt artificial insemination in pig, and are affected by farming context especially distance to artificial insemination provider centre. Farmer's intention to start for pig breeding also positively affects the intention to adopt the technology.